2013
DOI: 10.3109/15368378.2013.776430
|View full text |Cite
|
Sign up to set email alerts
|

Wi-Fi technology – an uncontrolled global experiment on the health of mankind

Abstract: The twenty-first century is marked with exponentially increasing development of technologies that provide wireless communications. To the pollution of the atmosphere with radio and TV signals, not only satellite communications but also any varieties of the Wi-Fi networks are added. By 2010 in the USA, 285 million mobile phone subscribers have been registered (for a little bit more than 300 million inhabitants). The estimate for the world is more than 5 billion mobile phone users at approximately 7 billion peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Moreover, T-cells isolated from pups showed no difference in proliferation with respect to the placebo animals. The complexity of the picture does not allow for the underestimation of possibly undiscovered adverse effects on developing biological systems [89], and these data must be evaluated in light of involuntary EMF environmental pollution exposure to children.…”
Section: The Effect Of Rf Exposure In Vivo: New Insights On Biosystemmentioning
confidence: 99%
“…Moreover, T-cells isolated from pups showed no difference in proliferation with respect to the placebo animals. The complexity of the picture does not allow for the underestimation of possibly undiscovered adverse effects on developing biological systems [89], and these data must be evaluated in light of involuntary EMF environmental pollution exposure to children.…”
Section: The Effect Of Rf Exposure In Vivo: New Insights On Biosystemmentioning
confidence: 99%
“…Rather they consider it as a wonderful tool for communication and entertainment. Taking into account the technological development in the wireless communications, will be fair to say that children at the age of 3-4 will be using mobile communication for many more years and with longer daily duration than their parents in the respect of entire life (Markov and Grigoriev, 2013).…”
Section: Children In Today's Rf Environmentmentioning
confidence: 99%
“…In an animal study, Hassanshahi et al [16] demonstrated that Wi-Fi radiation had possible adverse effects on cross-modal and unimodal novel object recognition. An important issue is the level of RF exposure from Wi-Fi in schools and public areas [17][18][19]. The International Commission on Non-Ionizing Radiation Protection published guidelines regarding the limits of exposure to non-ionizing radiations [20].…”
Section: Discussionmentioning
confidence: 99%